Individualized Considerations Regarding Sub-Superficial Musculoaponeurotic System Facelift Techniques - Joo Heon Lee (Archives of Aesthetic Plastic Surgery, 2016)
Based on a thorough understanding of facial structure around the superficial musculoaponeurotic system (SMAS), some types of sub-SMAS techniques have emerged to allow more harmonious rejuvenation procedures in the lower face and midface. These techniques are the Hamra composite facelift, the Stuzin extended SMAS technique, the Barton high SMAS technique, and the Ramirez subperiosteal facelift, each of which involves a specific dissection plane and is informed by distinct rationales with reasonable support. Each patient presents a unique facial structure and undergoes an individual rate of aging. The facial structures of East Asian faces, in particular, differ from those of Western faces. While emphasizing that the theory of structural mid-cheek anatomy is an essential part of facial rejuvenation, we would like to discuss the advantages and disadvantages of various sub-SMAS facelift techniques and to propose the most suitable techniques for a variety of individual faces.